"What are women's prisons for?" Gendered states of incarceration and history as an agent for social change. (2nd January 2017) - Halliday, Amy; Miller, Chelsea; Peterson, Julie
ABSTRACT: As the exhibition States of Incarceration: A National Dialogue of Local Histories travels the nation, visitors will explore the roots of mass incarceration in our communities. While mass incarceration has garnered increased media and scholarly attention in recent years, mainstream analyses overlook the role of gender, even as women are the fastest-growing segment of the incarcerated population in the United States. This article argues that women's incarceration and the gendered aspects of the carceral state need to become more prominent in the national narrative, and that museums and public history institutions, in partnership with local communities, have the potential to lead this effort. Archival research and oral history interviews with community activists on the ground shed light on the gendered aspects of incarceration in the United States while, at the same time, amplifying the voices of community members and activists. Doing so provides a model for how museums and public history professionals can become active participants in promoting social change.